Analysis of The Drivers Behind Nike’s Sneaker Market Decline and Its Response Strategics - Huang, Chenyi (Transactions on Social Science, Education and Humanities Research, 2025)
As the world’s largest global brand in the sneaker industry, Nike has suffered a decline in market share in the context of the industry’s overall growth in recent years. This study aims to analyse the main reasons for the decline in Nike’s sneaker market share and assess the response strategies. The survey demonstrates that rising competition in the industry, evolving tastes of the next generation of customers. And at the same time, Nike is simultaneously implementing a multifaceted response that consists of increasing product innovation, focusing on sustainability, modifying its marketing approach to reconnect with younger customers, and streamlining sales channels to bolster its direct-to-consumer presence. Based on a deep analysis of the relevant data and literature, this study shows that although Nike still has a huge influence in the market, Nike must continue to adapt to the changes in the market and make strategic adjustments and optimisations to maintain its leading position.